Proposed Process Changes In Product Development Process At Pharmaceutical Company - Mulyani Dwi Yanti; Leo Aldianto (Eduvest - Journal of Universal Studies, 2025)
This study investigates operational pain points and inefficiencies along to identify process-related changes within the current product development process of a pharmaceutical company, Imedco Djaja. The cycle of development new pharmaceutical products starting from formulation to registration until the product launched into the market, follows a linear and sequential process but suffered to adapt in delivering innovative, high-quality products while competing in time-to-market arrival and reducing intensive development costs. As the landscape demands evolves and the market pressure keep increasing, these business issues create both strategic and financial risks. The research applies Design Thinking as diagnostic tools, particularly Emphasize and Define to focus on problem identification and capture both the pain points and human-centric solutions. Furthermore, the study delves deeper in identifying the root causes of the deliverable delays and rising cost, which sometimes not only underlie on the technical failures, but hidden organizational barriers. The findings derived from both the semi-structured interview with internal cross-functional key stakeholders involved in product development process at Imedco Djaja exposed key issues such as how teams plan, misalignment in communicate between managerial and operations, overlapping and unclear roles, with low sense of the belonging over the projects. These insights examined using Directed Content Analysis (DCA), Thematic Analysis (TA), and Failure Mode and Effects Analysis (FMEA) to identify and prioritize most critical bottlenecks then address user-centric needs in providing potential process improvement.